Estimation of silage density in bunker silos by drilling - Wang, Ruonan (2012)
Abstract Silage density is an important factor in silage making. High density of silage in a silo implies a higher storing capacity and a high density of silage can also decrease the risk of dry matter losses due to air penetration into the silage. However, the density is often difficult to measure under practical conditions. In this study a method based on weighing drilled silage samples was evaluated. The method was tested on bunker silos with mainly grass/clover silage in four different farms in mid-Sweden. The drilled samples were collected by two methods: drilling by a 23.2 mm diameter drill (Stickit) and a 39.8 mm diameter drill (JTI). As the Stickit was a new device it was used twice for sampling. The resulting densities (calculated from the weight of the drilled samples and the volume of the hole in the silage created by the sampling) was compared with the densities derived from weighing silage blocks of 300-500 kg fresh weight using silo block-cutters with 1.5 to 2.3 meters width. The results showed that the correlation between the drilling methods was high and that both the JTI and the Stickit drill estimated the fresh weight density, the dry matter density and the dry matter content of silage blocks satisfactory. It was further concluded that the dry matter density depends on the dry matter content and the depth on which the sample is taken. The drilling operation must therefore represent the full silo depth to be able to estimate the density of the entire silo.